Cell source determines the immunological impact of biomimetic nanoparticles. (March 2016) - Evangelopoulos, Michael; Parodi, Alessandro; Martinez, Jonathan O.; Yazdi, Iman K.; Cevenini, Armando; van de Ven, Anne L.; Quattrocchi, Nicoletta; Boada, Christian; Taghipour, Nima; Corbo, Claudia; Brown, Brandon S.; Scaria, Shilpa; et al.
Abstract: Recently, engineering the surface of nanotherapeutics with biologics to provide them with superior biocompatibility and targeting towards pathological tissues has gained significant popularity. Although the functionalization of drug delivery vectors with cellular materials has been shown to provide synthetic particles with unique biological properties, these approaches may have undesirable immunological repercussions upon systemic administration. Herein, we comparatively analyzed unmodified multistage nanovectors and particles functionalized with murine and human leukocyte cellular membrane, dubbed Leukolike Vectors (LLV), and the immunological effects that may arise in vitro and in vivo . Previously, LLV demonstrated an avoidance of opsonization and phagocytosis, in addition to superior targeting of inflammation and prolonged circulation. In this work, we performed a comprehensive evaluation of the importance of the source of cellular membrane in increasing their systemic tolerance and minimizing an inflammatory response. Time-lapse microscopy revealed LLV developed using a cellular coating derived from a murine (i.e., syngeneic) source resulted in an active avoidance of uptake by macrophage cells. Additionally, LLV composed of a murine membrane were found to have decreased uptake in the liver with no significant effect on hepatic function. As biomimicry continues to develop, this work demonstrates the necessity to consider the source of biological material in the development of future drug delivery carriers.